KARAKTERISTIK SENSORI TEH CELUP MENIRAN (Phyllanthus niruri) DENGAN PENAMBAHAN DAUN STEVIA (Stevia rebaudiana) DAN DAUN MINT (Mentha piperita L.) SENSORY CHARACTERISTICS OF MENIRAN (Phyllanthus niruri) HERBAL TEA WITH THE ADDITION OF STEVIA LEAVES (Stevia rebaudiana) AND MINT LEAVES (Mentha piperita L.) - Cahyaningtyas, Fransiska Dyah Ayu; Murhadi, Murhadi; Zuidar, Ahmad Sapta; Hidayati, Sri (Jurnal Agroindustri Berkelanjutan, 2025)
Phyllanthus niruri (commonly known as meniran) is a medicinal plant that can be processed into herbal tea. However, it is limited by its less desirable sensory qualities, particularly in terms of taste, aroma, and color. This study aimed to investigate the effects of stevia and mint leaf additions, as well as their interaction, on the sensory characteristics of meniran herbal tea. A Completely Randomized Block Design (CRBD) was applied, consisting of two factors. The first factor was stevia leaf addition at three levels: S0 (0%), S1 (15%), and S2 (30%). The second factor was mint leaf addition at five levels: M0 (0%), M1 (15%), M2 (30%), M3 (45%), and M4 (60%). Data were analyzed using analysis of variance (ANOVA), followed by further analysis using orthogonal polynomial and orthogonal contrast tests at a 5% significance level. The results showed that both stevia and mint leaf additions had a highly significant effect on the sensory attributes of the tea. The interaction between these two factors significantly affected the color and overall acceptance, but not the taste and aroma. The best formulation was M4S2, which consisted of 60% mint and 30% stevia. This treatment produced a taste score of 4.25 (not bitter), an aroma score of 4.29 (not characteristically meniran), a color score of 1.29 (yellowish green), and an overall acceptance score of 3.34 (somewhat liked).